The immune response of the hepatopancreas against microsporidian infection in the oriental river prawn, Macrobrachium nipponense - Zhengfeng Ding; Shijie Yang; Xiangyue Xia; Jiarong Bao; Zhiyang Han (Aquaculture Reports, 2024)
Despite the economic and evolutionary significance of microsporidian species that infect aquatic hosts, little is known about how microsporidia interact with hosts. This study focused on Potaspora macrobrachium, a new microsporidium identified in the oriental river prawn, Macrobrachium nipponense. Gross pathology, histology with H.E. staining, and transmission electron microscopy (TEM) were performed to confirm the microsporidian infections. To learn more about the prawn anti-microsporidian response, de novo transcriptome sequencing of the hepatopancreas tissue—a significant source of innate immune molecules—was also conducted. The clean reads of the microsporidian-infected and control groups were 40.46 M and 40.83 M, respectively. 117,853 unigenes were functionally annotated using homology searches and six databases: Nr, Swiss-Prot, KEGG, eggNOG, Pfam, and G.O. 107 genes were considerably up-regulated, whereas 71 genes were down-regulated. The primary immune and metabolic signalling pathways, such as the ''MAPK signalling pathway,'' ''apoptosis,'' ''autophagy,'' ''endocytosis,'' ''lysosome,'' ''fatty acid biosynthesis,'' ''protein processing in the endoplasmic reticulum,'' ''spliceosome,'' and ''pancreatic secretion,'' were linked to the differentially expressed genes (DEGs). This implies that M. nipponense adopts various strategies to deal with microsporidian infection. To ensure the accuracy of the transcriptome data, eight DEGs were randomly chosen to participate in qRT-PCR validation. Additionally, single nucleotide polymorphisms (SNPs) and simple sequence repeats (SSRs) were detected within the gene library. These findings allow us to understand better the underlying processes governing the interactions of microsporidian parasites and the commercially important prawn, M. nipponense.